Primulina sichuanensis var. pinnatipartita (Gesneriaceae), a remarkable new variety from Chongqing, China - Kong, Hang-Hui; Zhou, Xi-Le; Zhou, Biao-Feng; Wen, Fang; Yang, Li-Hua (Phytotaxa, 2019)
Here, we describe and illustrate Primulina sichuanensis var. pinnatipartita, a new variety from southwestern China. This new variety is primarily distinguished from the type variety, P. sichuanensis var. sichuanensis, by its pinnatipartite leaf blade, a rare character in the genus Primulina. We show the morphological features of this new variety with illustrations and photographs.